Desain Kemasan Rappo dalam Membangun Cita-Cita Identitas Merek - Ramayanti, Dwi; Swatriani, Rinkapati (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
Rappo is a local brand that produces products, especially bags. A social enterprise that produces recycled plastic bag waste (kresek) that is designed in such a way that it becomes a product that has a selling value. Conceptually, a brand means a "contract" from a company to its customers; promises, benefits, quality and certain values. A well-designed brand identity is able to form a brand image with a positive perception in the minds of customers. The ideal of brand identity is a higher goal of a brand or organization that goes beyond the products and services it sells. There are nine aspects of the ideal of brand identity, namely vision, meaning, authenticity, differentiation, durability, coherence, flexibility, commitment, value. Rappo packaging design is one of the brand identity elements owned by Rappo. Researchers want to know the design of Rappo product packaging in building brand ideals. The research method used is qualitative, with research outputs in the form of journal publications. The results obtained at this time are that Rappo products are not optimal in packaging.